Deradicalisation to Combat Terrorism: Indonesia and Thailand Cases - Sumarwoto Sumarwoto; Mahmutarrom Mahmutarrom; Ifrani Ifrani (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Terrorism is a human-made disaster, which is usually in the form of organised crime. In prevention, terrorism cannot be done only through legal approaches alone but covers all aspects of society. While eradication aimed at combating terrorism, uncovering and addressing criminal cases and perpetrators of terror in the form of the establishment of the measures included in the crime of terror, handling, ranging up to the judicial investigation and threatened sanctions to perpetrators of terror. The method used is doctrinal with the statute approach, the conceptual approach, the historical approach, and the philosophical approach. The result shows that deradicalisation in Indonesia is carried out by BNPT for terrorists, families and sympathisers, while counter-radicalisation is carried out for the general public to increase the deterrent power of radical terrorism. In comparison, Thailand used the application of a curriculum in education as the concept of deradicalisation